Pengaruh Aktivitas Fisik dan Status Gizi terhadap Kemampuan Motorik pada Murid RA IKSAL Saok Laweh - Aisha Fitria; Wilda Welis; Anton Komaini; Liza; Ridho Bahtra (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study analyzed the influence of physical activity and nutritional status on the motor ability of students at RA IKSAL Saok Laweh. A quantitative descriptive-correlational design with a cross-sectional approach was employed. All 41 students were included through total sampling. Physical activity was assessed using a 16-item observation sheet, nutritional status was determined through anthropometric measurements based on body mass index-for-age, and motor ability was evaluated using 15 locomotor, non-locomotor, and manipulative tasks. Data were analyzed using descriptive statistics, validity and reliability testing, assumption tests, and multiple linear regression. Physical activity significantly predicted motor ability (t=6.057; p<0.001), and nutritional status also showed a significant effect (t=3.161; p=0.003). Both variables simultaneously produced a significant model (F=30.085; p<0.001), explaining 61.3% of the variance in motor ability (R²=0.613). Physical activity demonstrated a stronger relative contribution than nutritional status. The findings support adequate structured and unstructured movement opportunities, regular anthropometric monitoring, sufficient essential nutrient intake, and school-parent collaboration to promote motor development in early childhood.